2016
DOI: 10.1371/journal.pone.0150541
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Fibroblast Growth Factor Receptor 1 (FGFR1) in a Model of Spinal Cord Injury in Rats

Abstract: Spinal cord injury (SCI) is a severe condition that affects many people and results in high health care costs. Therefore, it is essential to find new targets for treatment. The fibroblast growth factor receptor 1 (FGFR1) signalling pathway has a history of being explored for SCI treatment. Several groups have examined the effect of high availability of different FGFR1 ligands at the injury site and reported corticospinal tract (CST) regeneration as well as improved motor functions. In this study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The AAV1 serotype is commonly used to transduce the CST via intracortical injections [31][32][33][34][35][36][37][38]. An earlier study that compared seven AAV serotypes (AAV1-AAV6, and AAV8) identified AAV1 and AAV5 as the best and secondbest serotypes to transduce the CST in rats [20].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…The AAV1 serotype is commonly used to transduce the CST via intracortical injections [31][32][33][34][35][36][37][38]. An earlier study that compared seven AAV serotypes (AAV1-AAV6, and AAV8) identified AAV1 and AAV5 as the best and secondbest serotypes to transduce the CST in rats [20].…”
Section: The Aav1 Serotype For Transduction Of the Corticospinal Tracmentioning
confidence: 99%
“…Traumatic spinal cord injury (SCI) is a devastating condition characterized by extensive tissue degeneration and severe neurological dysfunction, which affects 250,000 to 500,000 people worldwide1. In detail, 12,000 new cases of SCI occur every year in the USA, and the total number of American individuals living with SCI is estimated at ~259,000.…”
mentioning
confidence: 99%
“…We believe that the focus should shift towards more translatable techniques; however, it is clear that this is not trivial for a ligand that should be delivered very locally in high concentrations over a period of time. We, ourselves, have tried one alternative approach by injecting into the motor cortex adeno associated viruses (AAVs), a delivery method with the advantage of being already used in humans, however, still rather invasive [ 77 ]. Unfortunately, this treatment showed no beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…A different approach of exploring synergism between treatments was taken by ourselves. We hoped to combine the different effects that the various FGF ligands had by overexpressing their common receptor, the FGFR1 [ 77 ]. We did that in a rat model of unilateral pyramidotomy.…”
Section: Therapeutic Approaches Targeting the Fgfr Pathwaymentioning
confidence: 99%